2020
DOI: 10.1055/a-1164-6398
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy and safety of palliative esophageal stenting without fluoroscopy: a systematic review and meta-analysis

Abstract: Background and study aims Despite advances in curative treatments for esophageal cancer, many patients often present with advanced disease. Dysphagia resulting in significant weight loss and malnutrition leads to poor quality of life. Palliative esophageal stenting with self-expanding metal stents (SEMS) helps alleviate symptoms and prolongs survival. However, access to fluoroscopy may be limited at certain centers causing delay in patient care. Methods We searched multiple databases from inception t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 49 publications
0
10
0
1
Order By: Relevance
“…In a recent metaanalysis of palliative esophageal stent placement without fluoroscopy in 1778 patients from 17 studies, the pooled perforation rate was 1.2%, indicating the safety of this approach. 85 In the same study, retrosternal chest pain was found to be the most common AE reported (10.4%). In a retrospective review of 442 patients undergoing SEMS placement for dysphagia because of unresectable esophageal cancer, perforation occurred in .9% of patients.…”
Section: Perforationmentioning
confidence: 80%
“…In a recent metaanalysis of palliative esophageal stent placement without fluoroscopy in 1778 patients from 17 studies, the pooled perforation rate was 1.2%, indicating the safety of this approach. 85 In the same study, retrosternal chest pain was found to be the most common AE reported (10.4%). In a retrospective review of 442 patients undergoing SEMS placement for dysphagia because of unresectable esophageal cancer, perforation occurred in .9% of patients.…”
Section: Perforationmentioning
confidence: 80%
“…[9] SEMS placement for a malignant oesophageal stricture is considered a technical success, while the post-operative regression of dysphagia and the tolerance of enteral feeding are considered a clinical success. Chandan et al (2020) have recently conducted a meta-analysis and reported the technical and clinical success rates of oesophageal SEMS placement as 94.7% (95% CI 89.9-97.3) and 82.1% (95% CI 67.1-91.2), respectively. [10] In our sample, the technical success rate was 100%, probably because we used both fluoroscopy and endoscopy for the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to other studies regarding SEMS placement 8 24 , both the technical and clinical success rates were high. A recent meta-analysis from Chandan et al demonstrated the safety and efficacy of SEMS placement without fluoroscopy and reported rates of technical and clinical success of 94.7 % and 82.1 %, respectively 16 . Notably, our series has twice as many patients as the meta-analysis and further demonstrates the importance of high-volume centers in improving outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In many parts of the world, SEMS have traditionally been placed under fluoroscopy. However, there have also been multiple reports of SEMS stent placement under endoscopic visualization without fluoroscopy 14 15 16 , and at our institution, we further refined this and now place stents using a modified technique that utilizes measurements without either fluoroscopy or direct endoscopic visualization during stent deployment 15 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation